Transactions on Computational Science VIII - Gavrilova, Marina L.; Tan, C. J. Kenneth; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The 8th issue of the Transactions on Computational Science has been divided into two parts. Part I, prepared by Guest Editors Nadia Nedjah, Abdelhamid Bouchachia, and Luiza de Macedo Mourelle, consists of 5 detailed papers, presenting state-of-the-art research results on adaptive models for evolutionary computation and their application in various dynamic environments. The 6 papers in Part II take an in-depth look at selected computational science research in the areas of geometric computing, Euclidean distance transform, distributed systems, segmentation, visualization of monotone data, and data interpolation.
Environmental Modeling and Identification Based on Changes in Sensory Information -- Polymorphic Particle Swarm Optimization -- C-Strategy: A Dynamic Adaptive Strategy for the CLONALG Algorithm -- A Comparison of Genotype Representations to Acquire Stock Trading Strategy Using Genetic Algorithms -- Automatic Adaptive Modeling of Fuzzy Systems Using Particle Swarm Optimization -- Computational Algorithm for Some Problems with Variable Geometrical Structure -- In-Place Linear-Time Algorithms for Euclidean Distance Transform -- A Foundation of Demand-Side Resource Management in Distributed Systems -- Modified Bias Field Fuzzy C-Means for Effective Segmentation of Brain MRI -- Visualization of Monotone Data by Rational Bi-cubic Interpolation -- C1 Monotone Scattered Data Interpolation.
Keywords: Computer science; Computer software; Computational complexity; Information systems; Computer vision; Optical pattern recognition; Computer Science; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Pattern Recognition; Image Processing and Computer Vision; Information Systems Applications (incl.Internet).; Discrete Mathematics in Computer Science